Implikasi Game Edukasi 2D dan 3D : Mengenal Huruf dan Angka Terhadap Anak - Dania Eridani; Paulus Insap Santosa; Ridi Ferdiana (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
This paper contains the results of the developmentand implementation of educational games in 3D , as opposed to methods of learning using educational games 2D and conventional learning methods . The purpose of the application to determine the effectiveness of the use of each learning method and whether or not the development of educational game in 3D as a learning tool . Evaluation of the 91 respondents kindergarten class B of 4 kindergarten in Semarang , 28 respondents in the conventional learning , learning by 32 respondents on educational games 2D , and 31 respondents in the study with 3D educational game . Analysis of the results of the evaluation using the Kruskal - Wallis test . Evaluation material consists of 20 instructional materials related to letters and numbers and associated material response 5 user 3D educational game that will be used . The results of the Kruskal - Wallis analysis showed a difference in learning outcomes and figures hurud using educational games in 3D , 2D and educational game conventional learning . Response 31 users when playing 3D games are 87 % of respondents felt interested in playing games , 81 % of respondents are consistent in playing the game , 100 % of respondents felt the background music and animations used in the game interesting , and 97 % of respondents smoothly when using it with a computer game .